Currency Substitution in Developing Countries : An Introduction - Calvo, Guillermo; Vegh Gramont, Carlos (Washington, D.C. : International Monetary Fund, 1992)
This paper reviews the main policy and analytical issues related to currency substitution in developing countries. The paper discusses, first, whether currency substitution should be encouraged or not; second, how the presence of currency substitution affects the choice of nominal anchors in inflation stabilization programs; third, the effects of changes in the rate of growth of the money supply on the real exchange rate; fourth, the interaction between inflationary finance and currency substitution; and, finally, issues related to the empirical verification of the currency substitution hypothesis.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet